P108 Lung cancer resection outcomes in the first year: a 5 year review. (15th November 2016) - Ibrahim, J; Mukhopadhyay, A; Lostarakos, V; Mahmood, A; Khan, S; Maddekar, N; Hussain, I; Lea, A; Satur, C; Abid, Q; Ghosh, S; Haris, M
Abstract : Introduction: Lung cancer survival remains poor despite the use of advanced diagnostic and therapeutic interventions. Surgical resection offers the best chance of cure for those with early stage lung cancer. Those who undergo curative resection for non-small cell lung cancer remain at risk of recurrence. We wished to evaluate thoracotomy outcomes in patients undergoing resection with curative intent. Methods: Retrospective review of consecutive surgical resections for suspected or confirmed lung cancer over 5-year period between January 2010 and December 2014 in a tertiary thoracic unit. Patients referred from other centres were excluded. Surgical database and post-operative follow up information was reviewed. Futile thoracotomies were defined as inoperable lung cancer at the time of surgery, benign lung lesion, incomplete tumour resection margins and recurrence or death in the first year. 1 Results: 298 patients underwent surgical resection; mean age 68 years (range 26–91); male 150 (50%). 48 (16%) had histo-cytological confirmation of lung cancer prior to resection. Post-operative histology revealed 248 (83%) primary lung cancer; 31 (10%) benign pathology; 17 (6%) metastatic tumour from other primaries (breast, colorectal, bladder and renal) and 2 lymphomas. Of the 248 primary lung cancers, 88 (35%) had adjuvant chemotherapy and 27 (11%) had adjuvant radiotherapy including cranial irradiation. A total of 40/298 (13%) patients had recurrence in first year of which 20 died within 1 year. Based on previously used definition, 1 the futile thoracotomy rate was 33% (99/298) – see Table 1 . If surgical resection of benign lesions is considered diagnostic, the futile thoracotomy rate would be 23% (68/298). Conclusion: The definition of futile thoracotomy is debatable, but the risk remains high. Prior to surgery every effort should be made to minimise the risk by using combined staging modalities including minimally invasive diagnostic tools and appropriate patient selection. Reference: Fischer B, Lassen U, Mortensen J, et al . Preoperative staging of lung cancer with combined PET-CT. N Engl J Med 2009;361 :32–9.